Reflections about gender differences in girls' delinquency behaviors in Chile - Marcela Pilar Aedo Rivera; Patricia Varela Pino (Oñati Socio-Legal Series)
This article presents the main findings of a study commissioned by the Office of the Undersecretary of Crime Prevention, under the Ministry of the Interior of Chile, and reflect on gender differences in the infringing behavior of girls and adolescents, especially those who enter the Family Integral Care Program (PAIF) 24 hours. The interpretative framework used for the analysis of it is that of feminist criminology and from this perspective it is considered how girls and adolescents have been historically relegated in the studies on juvenile delinquency and the need to incorporate in them the gender stratification in the patriarchal society. Especially in order to identify gender differences in adolescent female crime and its treatment.